Feedback function of the stimulus situation, the response, and the consequence - María Ximena Moreno Yescas; Daniel Rentería Cárdenas; Alan René Loquay Ramsauer; Gerardo Alfonso Ortiz Rueda (Mexican Journal of Behavior Analysis, 2024)
This study is framed within the taxonomy for the analysis of descriptions proposed by Ortiz et al. (2008). This study aimed to analyze the acquisition of the feedback function of each component of a situation (i.e. stimulus situation, response, and consequence) presented as informative messages in a first-order matching-to-sample task with geometric figures. Participants were exposed to said messages after each trial and made pre-contact and post-contact descriptions periodically. It was observed that the participants exposed to the informative messages which included the Consequence component followed the correct matching criteria in the task, as opposed to the rest of the groups. This is discussed in terms of the acquisition of the feedback function following the performances in the pre and post-test and the transfer tasks.